ANALISIS HUMAN CAPITAL READINESS PADA PERUSAHAAN PERDAGANGAN INDONESIA (PERSERO) - Sri Handayani (Universitas Agung Podomoro, 2017)
This research aims to review the gaps between human capital employed and the actual needs of PT. PPI (Ltd.) in achieving the corporate objectives. The Company is built with the vision and mission that are translated into corporate actions towards the achievement of corporate goals. The company's mission must be communicated clearly to all stakeholders, especially employees, because employees play an important competency for successful mishievin. Through this study, the HR department is expected to be able to measure the contribution of human capital in the process of achieving corporate goals. The measurement is intended to allow the HR department to provide and develop competence in accordance with company requirements, to achieve corporate objectives. The results of this study conclude that the availability of human capital PT. PPI (Ltd.) only reached 65 percent. By that illustrated, the percentage of PT. PPI (Ltd.) doesn’t have the human capital needs in the achievement of company goals, so PT. PPI (Ltd.) needs a strategic initiative to address the inconsistency, which are recruitment and training on the job strategies in the company.